Quality of life outcomes in adults with moderate‐to‐severe plaque psoriasis treated with dimethylfumarate (DMF): a post hoc analysis of the BRIDGE study. (17th October 2019) - van de Kerkhof, P.C.M.; Loewe, R.; Mrowietz, U.; Falques, M.; Pau‐Charles, I.; Szepietowski, J.C.
Abstract: Background: Psoriasis is a chronic inflammatory skin disease associated with quality of life (QoL) impairment. BRIDGE was a randomized, double‐blind, phase III study comparing the efficacy and safety of dimethylfumarate (DMF) with a fixed combination of fumaric acid esters (FAE) or placebo for the treatment of moderate‐to‐severe psoriasis. Objectives: This post hoc analysis investigated treatment effect on QoL overall and by patient subgroups categorized by disease severity. Week 8 efficacy responses were also investigated as possible predictors of Week 16 Dermatology Life Quality Index (DLQI) outcomes. Methods: Patients were randomized to receive a maximum daily dose of 720 mg of DMF, FAE (gradual up‐titration) or placebo for 16 weeks. Psoriasis Area Severity Index, Body Surface Area, Physician's Global Assessment and DLQI were assessed at baseline, Weeks 8 and 16. DLQI 0‐1 indicated 'no effect on patient life'. Associations between baseline severity, Week 16 DLQI and Week 8 efficacy (as observed cases) were also examined. Results: At baseline, 671 patients were included in the full analysis set (267 randomized to DMF, 273 to FAE and 131 to placebo). DMF was superior to placebo ( P < 0.001) and not significantly different to FAE regarding Week 16 DLQI outcomes ( P > 0.05). Baseline disease severity did not impact DLQI outcomes at Week 16. In DMF‐ and FAE‐treated patients, Week 8 PASI 50/75 responders reported better DLQI responses at Week 16 vs non‐responders ( P < 0.05). Week 8 PASI ≤ 3 and/or PGA 0‐1 responders were also more likely to report DLQI 0‐1 at Week 16 vs non‐responders ( P < 0.05). Conclusion: Dimethylfumarate significantly improved DLQI outcomes vs. placebo and was not affected by baseline disease severity. Efficacy responses (PASI 50/75, PASI ≤3 and PGA 0‐1) as early as Week 8 were predictive of QoL outcomes at Week 16 in DMF‐ and FAE‐treated patients.